THE SIGNIFICANCE OF LITERARY CHARACTERS IN THE WORKS OF CHARLES DIKCENS - Qodirova Shaxlo Qobiljon qizi; Bahodir Aliqulovich Kholiqov (TADQIQOTLAR, 2025)
Abstract This  article  explores  the  significance  of  literary  characters  in  the  works  of Charles  Dickens.  Through  an  analysis  of  novels  such  as  Oliver  Twist,  David Copperfield,  Great  Expectations,  and  Hard  Times,  the  study  demonstrates  how Dickens employs characters not only to develop his plots but also to critique the moral, social, and psychological aspects of Victorian society. The article argues that Dickens' mastery of character development is one of the key reasons his novels remain impactful and relevant today.